Management in Perspective: Management and Organization In Japanese Industry - Froomkin, Joseph (Academy of Management Journal, 1964)
The article describes the management and organizational practice by businesses in Japan. Corporations in Japan have little formal organization, less delegation of authority and little reliance on staff work. Despite this lack of an accepted or recorded theory of organization, most Japanese firms follow a single pattern in their organization and employment practices. A discussion is presented about economic aspects of Japanese industry and the integration of social values into Japanese business practices.